Isozyme alterations in soybean cultivar seeds at different storage conditions - Carvalho, Everson Reis; Mavaieie, Denilson Paulo da Rosa; Oliveira, João Almir; Carvalho, Marcos Vinícios de; Vieira, Antônio Rodrigues (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to determine the physiological and isozyme alterations in seeds of soybean genotypes, under different storage conditions. A completely randomized experimental design was used with four replicates, in a factorial arrangement with six soybean cultivars (TMG 1176, TMG 1179, TMG 132, TMG 133, TMG 115, and GB 874) and five storage times (0, 2, 4, 6, and 8 months), in two storage environments (a cold and dry chamber, at 10ºC and 50% relative humidity; and a conventional warehouse, under uncontrolled conditions). Physiological quality was evaluated by the germination, accelerated aging, and cold tests. Isozyme expressions of malate dehydrogenase (MDH), alcohol dehydrogenase (ADH), esterase (EST), isocitrate lyase (ICL), superoxide dismutase (SOD), and peroxidase (PO) were determined. Soybean seeds stored in cold and dry chambers maintained their physiological quality. After six months storage under uncontrolled conditions, seed quality and isozyme expressions of MDH, ADH, EST, ICL, SOD, and PO lowered. There was no alteration on seed stored in cold and dry chambers. Soybean genotypes show different tolerance levels to storage and isozyme expression.